Posmodernisme Sastra dalam Novel Kita Pergi Hari Ini Karya Ziggy Zezsyazeoviennazabrizkie - Nopita; Legi Elfitra; Ahada Wahyusari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The study discusses literary postmodernism contained in the literary work of in the novel We GO Today by Ziggy Zezsyazeoviennazabrizkie. The aim of this research is to describe the criticism of literary postmodernism in. in the novel We GO Today by Ziggy Zezsyazeoviennazabrizkie The method used in this research is descriptive qualitative. The data in this study are in the form or words or sentences contained in the novel We Go Today by Ziggy Zezsyazeoviennazabrizkie. The data collection techniques used to obtain research data are note-taking and observing technique. The data analysis technique used is content analysis bt reading, analyzing, describing, and concluding the contents of the data found in the novel We GO Today by Ziggy Zezsyazeoviennazabrizkie. Theses data are found in quotations taken from narratives or dialogues between characters. The result of this study are that the are criticisms of literary postmodernism in the form oq 1) capitalism with various characteristics such as spontaneousness, fact, and gesture, 2) Parody with satire and irony, 3) reification with findings on the nature of social reality and cultural phnenomena.